Developing Early Childhood Discipline through the Habituation of Shalat Dhuha at Raudhatul Athfal Fatimah Az-Zahra Mulia - Sari, Ika Destiana; Sa’adah, Latifatus; Al Ghofiqi, Moh. Imam Mudi (Global Education Journal, 2025)
This study aims to explore the role of habituating congregational dhuha prayer in fostering discipline among early childhood students at RA Fatimah Az-Zahra Mulia Randublatung Blora. Employing a qualitative method with a case study approach through observation and interviews, the findings reveal that the routine practice of congregational dhuha prayer has a positive impact on children’s discipline development. The students become accustomed to arriving on time, lining up orderly, following instructions, and consistently performing worship. Challenges encountered include low participation, limited internal motivation, and insufficient parental involvement. Through engaging approaches, teacher role modeling, and parental collaboration, this activity proves effective in instilling discipline while simultaneously strengthening children’s religious character from an early age.